Hand hygiene by health professionals: a literature review (Research, Society and Development, 2021)
Introduction: According to the World Health Organization (WHO), the hands of health professionals are one of the main mechanisms of transmission of hospital infections, which can be called cross infections. Objective: To present proper hand hygiene as an effective method to reduce the prevalence of hospital infections. Methodology: This study is a bibliographical, descriptive-analytical review. Results and Discussion: Hand hygiene is a low-cost, practical and simple prophylactic method, as it reduces the likelihood of nosocomial infections, and should be reinforced among health professionals. The consequences of non-hand hygiene or hygiene by incorrect technique can lead to an increase in hospital infections, burdening the health system, and increasing the period of institutionalization of patients and the relative and absolute morbidity and mortality rates. Conclusion: The action on possible factors that incur the absence or incorrectness of the practice of hand hygiene, as well as the reaffirmation of the importance of hand hygiene among the health team is necessary for the reduction and control of hospital infections.